A mathematical approach to the evaluation of international diversification for the South African investor - Van den Honert, Robin Charles (Department of Statistical Sciences, 2016)
This thesis attempts to isolate the major markets for investment outside South Africa, and to determine what proportion of a South African investor's capital, if any, should be held in foreign securities under different possible restrictions laid down by the South African Reserve Bank. The main argument advanced in favour of foreign investment is risk reduction through diversification.